Open access and biodiversity conservation: challenges and potentials for the developing world - Jitendra Gaikwad; Vishwas Chavan (Data Science Journal, 2006)
Access to and sharing of data is essential for biodiversity conservation. However, workers from developing nations that harbor rich biodiversity often do not have access to biodiversity information and often are not keen on making what data they have accessible to others. Open access initiatives offer a great opportunity to make the world's biodiversity information accessible to anyone, at any time and in any place. This article reviews the state of open access in the developing world and argues for the increase of data on biodiversity in the public domain. It makes specific suggestions about how the developing world can reap the benefits of this global S&T movement to better conserve and sustain biotic resources through the creation of a "virtual biodiversity research space".